Inside Back Cover: Circularly polarized luminescence of agglomerate emitters. Issue 5 (22nd October 2021) - Zhang, Chong; Li, Si; Dong, Xi‐Yan; Zang, Shuang‐Quan
Abstract : CPL‐active agglomerate materials with unique polarization have promising applications in 3D optical displays, encryptions, biological probes, chiral photoelectric devices, and CPL switches. This review systematically summarizes advances in CPL of aggregate and solid materials, and will give inspiration for the design and application of CPL‐exhibiting agglomerate materials. ( Aggregate . 2021;2:e48 )